Optimization and Implication of Adipose-Derived Stem Cells in Craniofacial Bone Regeneration and Repair - Cong Gu; Qinghuang Tang; Liwen Li; YiPing Chen (Bioengineering)
Adipose-derived stem cells (ADSCs) have emerged as a promising resource for craniofacial bone regeneration due to their high abundance and easy accessibility, significant osteogenic potential, versatile applications, and potential for personalized medicine, which underscore their importance in this field. This article reviews the current progress of preclinical studies that describe the careful selection of specific ADSC subpopulations, key signaling pathways involved, and usage of various strategies to enhance the osteogenic potential of ADSCs. Additionally, clinical case reports regarding the application of ADSCs in the repair of calvarial defects, cranio-maxillofacial defects, and alveolar bone defects are also discussed.